2005
DOI: 10.1002/dvdy.20431
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish R‐cadherin (Cdh4) controls visual system development and differentiation

Abstract: In zebrafish, R-cadherin (cadherin-4 or Cdh4) is expressed in the retina and in retinorecipient brain regions, suggesting that Cdh4 functions during visual system development. Cdh4 function was examined during retinogenesis and retinal axon outgrowth using antisense morpholino oligonucleotides and mutant Cdh4 construct expression. In knockdowns, Cdh4 was reduced or absent, eyes were small, and retinae lacked discrete laminae. Increased cell death produced the small eye phenotype. Zn5-, Pax6-, and zpr-1-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 51 publications
7
74
1
Order By: Relevance
“…These embryos were similar to the moderately to severely affected embryos shown in our previous study (Babb et al, 2005). Moreover, zn5 (an antibody that labels differentiating neurons and their processes) or acetylated tubulin antibody (that labels ␣-tubulin) immunostaining demonstrated that these embryos had a much reduced retinal ganglion cell layer and retinal axons, as reported in our study of Cdh4 function in zebrafish visual system development (Babb et al, 2005). Embryos injected with lower concentrations of the MOs (0.125 mM, 1.0 ng/embryo for RcadMphA, 0.06 mM, 0.5 ng/embryo for RcadMphB) were largely indistinguishable from control embryos.…”
Section: Cdh4 Is Involved In the Formation Of The Cranial And Lateralsupporting
confidence: 89%
See 4 more Smart Citations
“…These embryos were similar to the moderately to severely affected embryos shown in our previous study (Babb et al, 2005). Moreover, zn5 (an antibody that labels differentiating neurons and their processes) or acetylated tubulin antibody (that labels ␣-tubulin) immunostaining demonstrated that these embryos had a much reduced retinal ganglion cell layer and retinal axons, as reported in our study of Cdh4 function in zebrafish visual system development (Babb et al, 2005). Embryos injected with lower concentrations of the MOs (0.125 mM, 1.0 ng/embryo for RcadMphA, 0.06 mM, 0.5 ng/embryo for RcadMphB) were largely indistinguishable from control embryos.…”
Section: Cdh4 Is Involved In the Formation Of The Cranial And Lateralsupporting
confidence: 89%
“…By 50 -55 hpf, the majority of the cdh4 morphants (716/867, 86.6%) showed a similar gross morphology to the control embryos, except that the cdh4 morphants had eyes of reduced size, although some were only slightly smaller, and some had slightly ventrally curled tails. These embryos were similar to the moderately to severely affected embryos shown in our previous study (Babb et al, 2005). Moreover, zn5 (an antibody that labels differentiating neurons and their processes) or acetylated tubulin antibody (that labels ␣-tubulin) immunostaining demonstrated that these embryos had a much reduced retinal ganglion cell layer and retinal axons, as reported in our study of Cdh4 function in zebrafish visual system development (Babb et al, 2005).…”
Section: Cdh4 Is Involved In the Formation Of The Cranial And Lateralsupporting
confidence: 88%
See 3 more Smart Citations